Red Herrings and the “Stench of Fish”: Subverting “Praise” in Thomas Nashe’s Lenten Stuffe - Bennett, Kristen Abbott (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
In Lenten Stuffe, “praise” emerges as a red herring diverting readers from recognizing how Thomas Nashe telescopes his chorography of Yarmouth into a catalogue of arbitrary Crown rule from William the Conqueror’s rule through the English Reformation. So too is Nashe’s apology for contributing to the seditious play, Ile of Dogs. Historical circumstances surrounding the Swan Theatre and a stolen diamond complicate conventional readings of this incident, Nashe’s exile, and subsequently, the sincerity of Nashe’s encomium. Lastly, this essay examines Nashe’s projection of the Butcher and Fishmonger’s debate surrounding the arbitrariness of Lenten laws from Erasmus’s colloquy “A Fish Diet” into the red herring’s fictional ascent to human and divine monarchy. Erasmus’s joke in “Fish Diet” is at the expense of the Fishmonger, but Nashe elides his geographical and political targets to generate a subtext of outrage directed at Crown rule and English Reform.